2009
DOI: 10.1007/s10295-009-0669-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysing overexpression of l-valine biosynthesis genes in pyruvate-dehydrogenase-deficient Corynebacterium glutamicum

Abstract: L-valine biosynthesis was analysed by comparing different plasmids in pyruvate-dehydrogenase-deficient Corynebacterium glutamicum strains in order to achieve an optimal production strain. The plasmids contained different combinations of the genes ilvBNCDE encoding for the L-valine forming pathway. It was shown that overexpression of the ilvBN genes encoding acetolactate synthase is obligatory for efficient pyruvate conversion and to prevent L-alanine as a by-product. In contrast to earlier studies, overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…50%) and relatively low final titers of 2-ketoisovalerate (55 mM) and L-valine (22 mM). The same strain overexpressing ilvE (instead of ilvD) formed only 10 mM 2-ketoisovalerate (Y P/S of 0.052 mol per mol of glucose) and 104 mM L-valine (3). In combination, these results indicate the importance of the transaminase B for L-valine formation and point to the contribution of the ilvE deletion to the production of 2-ketoisovalerate.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…50%) and relatively low final titers of 2-ketoisovalerate (55 mM) and L-valine (22 mM). The same strain overexpressing ilvE (instead of ilvD) formed only 10 mM 2-ketoisovalerate (Y P/S of 0.052 mol per mol of glucose) and 104 mM L-valine (3). In combination, these results indicate the importance of the transaminase B for L-valine formation and point to the contribution of the ilvE deletion to the production of 2-ketoisovalerate.…”
Section: Discussionmentioning
confidence: 78%
“…In fact, overexpression of ilvBNCD and, in particular, the deletion of pqo shifted the carbon flux significantly in the direction of 2-ketoisovalerate, leading to higher final titers of this product and only low concentrations of the by-products pyruvate, Lalanine, and L-valine. The overexpression of ilvBNC or ilvBNCD in C. glutamicum ⌬aceE has previously been shown to be necessary for a more efficient carbon flux from pyruvate toward L-valine (3,6,40). However, even the pJC4-based overexpression of ilvBNCD might not necessarily completely overcome a limitation in this pathway since expression of ilvBNC is partially controlled by an attenuation mechanism involving antitermination (34).…”
Section: Discussionmentioning
confidence: 99%
“…Bartek et al [1] and Blombach et al [3] demonstrated that overexpression of the ilvBNC operon with the ilvE gene afforded higher L-valine production than overexpression of the ilvBNC operon with the ilvD gene. To study the separate contributions of ilvB, ilvN r , ilvC, and livE genes to the production of L-valine, the stains of B. flavum ATCC14067/ pDXW-8-ilvBN r , B. flavum ATCC14067/pDXW-8-ilvBN r C, B. flavum ATCC14067/pDXW-8-ilvEBNC, B. flavum ATCC 14067/pDXW-8-ilvEBN r C, and B. flavum ATCC14067/ pDXW-8-ilvE were constructed, fermentations with the resulting strains were carried out at 31, 34, 37, and 40°C with the fermentation with B. flavum ATCC14067 as control experiment.…”
Section: Effect Of Overexpression Of Different Ilv Genes On L-valine mentioning
confidence: 98%
“…TA catalyzes the conversion of 2-oxo-isovalerate into L-valine with L-glutamate as the amino group donor [15]. Overexpression of the ilvBNC operon with the ilvE gene afforded higher L-valine production than overexpression of the ilvBNC operon the with ilvD gene [1,3]. AHAS is feedback-inhibited by three branched-chain amino acids; the 50% inhibitory concentrations for AHAS with valine, isoleucine, and leucine have been determined (0.9, 3.1, and 6 mM, respectively) [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation